Pengaruh Financial Knowledge, Financial Attitude, Dan Digital Financial Literacy Terhadap Financial Behavior Pengguna E-Payment Di Provinsi Jawa Timur - Shela Dwi Widhya Sari; Ulil Hartono; Harlina Meidiaswati (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study aims to analyze the influence of financial knowledge, financial attitude, and digital financial literacy on the financial behavior of Generation Z e-payment users in the Gerbangkertosusila area, East Java Province. The study is motivated by the increasing use of digital payment services that require individuals to manage their finances wisely in the digital era. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 264 respondents selected using purposive sampling techniques. The analysis method used was Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that financial knowledge, financial attitude, and digital financial literacy have a positive and significant effect on financial behavior. Digital financial literacy was found to have the strongest influence on financial behavior among Generation Z e-payment users. These findings support the Theory of Planned Behavior, Social Cognitive Theory, and Human Capital Theory, which explain that financial behavior is influenced by cognitive, attitudinal, and literacy factors. This study implies that improving financial literacy and financial attitudes can encourage more responsible financial behavior in the digital financial environment.